Deep Incarnation and Kenosis: In, With, Under, and As: A Response to Ted Peters. (2nd September 2013) - Gregersen, Niels Henrik
Abstract: In this response to Ted Peters, I relate the proposal of deep incarnation to Luther's theology of the real presence of the humanity of Christ in creation. Based on a typology of four distinctive models of kenosis, I furthermore argue that a kenotic view of incarnation and divine creativity does not necessarily imply a divine absence and withdrawal from creation, as presupposed by Professor Peters. Deep incarnation is consistent with a compatibilist view of kenosis, but not with ideas of divine abdication, or metamorphosis. Finally I situate the view of deep incarnation to Scandinavian creation theology and to research programs at the Centre for Naturalism and Christian Semantics, Copenhagen University.